Annual variations in hepatic antioxidant defenses and lipid peroxidation in a temperate fish, common bream Abramis brama (L.) - Alexey A. Morozov; Grigorii M. Chuiko; Victoria V. Yurchenko (International Aquatic Research, 2017)
Abstract Alternation of physiological states during the annual cycle (pre-spawning mobilization, spawning energy loss, post-spawning accumulation of energy reserve, declined metabolic activity during the wintering) occurring in the wide temperature range requires high plasticity of fish defense systems. The article presents a 2-year study of hepatic antioxidant defenses and lipid peroxidation in the temperate cyprinid fish, common bream Abramis brama (L.), in relation to basic annual rhythms, such as photoperiodic and temperature cycling, reproduction and feeding activity. The objective of the study was to evaluate the plasticity of antioxidant defenses in bream under normal conditions throughout the annual cycle, by measuring hepatic antioxidants (superoxide dismutase, catalase, glutathione-S-transferase activities and reduced glutathione concentrations) and products of lipid peroxidation (thiobarbituric acid reactive substances concentrations). The results suggested that hepatic levels of antioxidants in bream varied dramatically during the annual cycle allowing bream to develop necessary adaptation and implement reproduction program. The lowest values of all studied antioxidants were witnessed in the middle of winter. In early spring, antioxidant enzyme activities increased rapidly reaching their maxima in late spring and summer. Toward the end of autumn, enzyme activities were declining toward the levels observed before the ice breakup. Spring–summer up-regulation of antioxidant defenses along with increased lipid peroxidation indicated bream to be experiencing mild oxidative stress.